ChemInform Abstract: [Ni(NHC)]‐Catalyzed Cycloaddition of Diynes and Tropone: Apparent Enone Cycloaddition Involving an 8π Insertion. Issue 24 (June 2015) - Kumar, Puneet; Thakur, Ashish; Hong, Xin; Houk, K. N.; Louie, Janis
Abstract: The reaction tolerates a broad variety of functional groups and proceeds with excellent regioselectivity in most cases.